Tunable broadband light emission from graphene. (3rd May 2021) - Ghirardini, Lavinia; Pogna, Eva A A; Soavi, Giancarlo; Tomadin, Andrea; Biagioni, Paolo; Dal Conte, Stefano; Mignuzzi, Sandro; De Fazio, Domenico; Taniguchi, Takashi; Watanabe, Kenji; Duò, Lamberto; Finazzi, Marco; et al.
Abstract: Graphene is an ideal material for integrated nonlinear optics thanks to its strong light–matter interaction and large nonlinear optical susceptibility. It has been used in optical modulators, saturable absorbers, nonlinear frequency converters, and broadband light emitters. For the latter application, a key requirement is the ability to control and engineer emission wavelength and bandwidth, as well as electronic temperature. Here, we demonstrate that the emission wavelength of graphene's broadband hot carrier photoluminescence can be tuned by integration in photonic cavities, while thermal management can be achieved by out-of-plane heat transfer to hexagonal boron nitride. Our results pave the way to graphene-based ultrafast broadband light emitters with tunable emission.